SUSTAINABILITY STUDY OF TRADITIONAL BECAKS AS PART OF TOURISM IN CITY OF YOGYAKARTA - Fauzan Iscahyono, Achmad
Sustainability is a concept that has developed and is widely used to solve a problem as a whole, which involves environmental, economic and social aspects (Purnama, 2011). One of strategies that can be developed in the concept of sustainability is by providing alternative transportation modes in addition to public transportation modes that are capable of carrying many passengers or goods. One of the alternative modes of transportation is becak (similar like pedicab) mode which is also one of the modes of paratransit transportation. In Indonesia, the city of Yogyakarta is one of the cities that uses becak as a tourist attraction. The traditional becak in the city of Yogyakarta is a traditional mode of transportation that has a distinctive model and has become a part of the culture that is closely related to the history of Javanese culture because it is associated with the kingdom. In addition to supporting the tourist movement, the existence of becaks in the city of Yogyakarta still has an important role in fulfilling the mobility of small communities and also supports economic activities, such as transportation services for people and goods or cargo, especially the types of traditional becak. The sustainability of the existence of traditional becak in the city of Yogyakarta has been able to survive for decades until now. This raises the suspicion that the sustainability of the existence of traditional becaks as part of tourism in the city of Yogyakarta tends to be due to the fulfillment of preparedness in certain aspects included in the concept of sustainability transportation, such as economic, social, and environmental aspects. Therefore, the aim of this study was to identify the sustainability conditions of traditional becaks as part of tourism in the city of Yogyakarta and the factors that support the sustainability of the existence of traditional becaks in the city and potentially be applied in other areas. The methodology used is content analysis method, descriptive analysis method, spatial analysis using Geographic Information Systems (GIS) software, and Social Network Analysis (SNA) using UCINET and NetDraw software. Based on the results of the analysis that has been carried out, the factors that influence the sustainability of the existence of traditional becaks in the city of Yogyakarta and their application can be applied in other regions tend to be factors included in the social aspects, which include: 1) The existence of social network in the informal sector in the form of relations of kinship-based social institutions that have been entrenched between traditional becak drivers and business actors; 2) Support from the formal sector in promoting efforts to regulate traditional becaks, both in the form of regulations governing the existence of traditional becaks, as well as other provisions; and 3) Engagement of various stakeholders and community groups in the process of planning and managing the traditional becak transportation system.